Effects of Mogroside V on Quality and Antioxidant Activity of Boar Frozen–Thawed Sperm - Heming Sui; Xin Wang; Kunlong Hu; Xiaoyu Zuo; Haonan Li; Zhengyu Diao; Jiajing Feng; Yunhai Zhang; Zubing Cao (Antioxidants, 2025)
Cryopreserved pig semen tends to produce excessive reactive oxygen species (ROS) during the thawing process, which leads to a decline in semen quality during in vitro storage. Mogroside V (MV) has been proven to be an effective antioxidant, and previous research has shown that MV can delay oocyte aging and improve the in vitro maturation efficiency of pig oocytes. However, the role of MV in the cryopreservation capacity of animal sperm remains unclear. To evaluate the effect of MV on sperm motility after thawing, different concentrations of MV (0, 25, 50, 75, 100 μmol/L) were added to the thawing medium. By comparing the sperm motility and kinematic parameters in the thawing medium with different MV concentrations and incubation times (0, 1, 2, and 4 h), we ultimately selected sperm thawed immediately in the medium supplemented with 75 μmol/L MV for subsequent experiments. Compared with the control group, the sperm thawing medium containing MV improved sperm quality during the freeze–thaw process. Immediate evaluation after thawing at 37 °C showed that supplementation with 75 μmol/L MV produced an optimal effect on the maintenance of motility, plasma membrane integrity, the acrosome integrity, the ROS levels, and the T-AOC activity. In conclusion, MV supplementation improves the quality of frozen–thawed sperm by enhancing sperm function and preventing oxidative stress.